Increased expression of pap and sfa Genes in Biofilm-Forming Uropathogenic Escherichia coli Associated with Urinary Tract Infections - Purbowati, Rini; Utami, Sri Lestari (Molecular and Cellular Biomedical Sciences, 2025)
Background: Urinary tract infections cover a broad spectrum of infectious syndromes and affect the urinary tract from the urethra to the kidneys. Generally caused by uropathogenic Escherichia coli (UPEC), and their pathogenesis is greatly influenced by biofilm formation, which results in persistent and recurrent infections. UPEC uses filamentous adhesive structures such as pili or fimbriae, pyelonephritis-associated pili, and S fimbriae, which are regulated by the pap and sfa operons, respectively. The purpose of the study was to detect the effects of two virulence genes, (pap 7 and sfa 9) on biofilm-forming UPEC associated with urinary tract infections.Materials and methods: A total of 123 UPEC isolates were collected from clinical microbiology laboratory section of a general hospital in Surabaya, Indonesia. Urine samples yielded UPEC with significant counts (≥105 CFU/ml), and the biofilm development was analyzed using the Congo red agar method. The presence of pap 7 and sfa 9 genes in the isolates was determined using PCR assay. Results: Among the 123 UPEC isolates, 66 isolates were able to form biofilms, as determined using the Congo red agar (CRA) method. Biofilm-forming UPEC isolates exhibited a high positivity frequency for the pap 7 gene (65.85%), while the positivity frequency for the sfa 9 gene was significantly lower (14.63%).  Conclusion: An increase in th expression of pap 7 and sfa 9 are is associated with the ability to form biofilms, which could serve as a diagnostic marker for biofilm formation potential vaccine target.Keywords: biofilm, pap, sfa, uropathogenic, Escherichia coli, UTI